Long Bean Leaf Extract for Improving Haematological Status of Female Adolescent with Anemia that Gets Fe Supplementation - Nurjanah, Fatihah Wari; Hadisaputro, Suharyo; Fatmasari, Diyah (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The incidence of anemia among female adolescent in Indonesia is 48.9%, due to menstruation, poor nutrition intake and worm investment. Long-term effects of anemia in female adolescent can occur stunting. Pharmacological anemia management by taking Fe supplements but these supplements can cause nausea. Nausea can be avoided by non-pharmacological anemia treatment by consuming Fe-containing foods such as long bean leaves. Long bean leaf contains Fe which can accelerate the absorption process of it in the body. The objective of the research was to analyze the effect of long bean leaf extract on changes in anemia status of female adolescent given Fe supplementation. Quasy experiment research design with pretest posttest with control group design. Data was collected for 14 days with 38 respondents. The treatment group was given 200 mg / day long bean leaf extract and Fe supplement, while the control group was given Fe supplement. Hemoglobin, hematocrit and erythrocyte levels were measured before and after the intervention. Data analysis used paired and independent sample t tests. The results showed the treatment group experienced increased levels of hemoglobin, hematocrit and erythrocytes by 1.45 gr / dL (p: 0.02), 3.61% (p: 0.019) and 0.53 x 106 / Ã‚Âµl (p: 0.013 ). 200 mg / day long bean leaf extract given to young women with anemia who received iron supplementation for 14 days improved hematological status as indicated by an increase in hemoglobin levels, hematocrit and erythrocyte counts.